One size doesn't fit all: religious/spiritual identities moderate salutary effects of religion. Issue 2 (7th February 2021) - Speed, David; Fowler, Ken
ABSTRACT : Religious/spiritual beliefs and behaviours are frequently described as having salutary effects, but there are likely unexplored exceptions to this general finding. We combined data from the 2011/2012 Canadian Community Health Surveys ( N  > 7077) to investigate how religion/spirituality predicted five health outcomes (i.e., three subscales on the Mental Health Continuum – Short Form, self-rated health, and satisfaction with life), and whether these relationships were moderated by a person's religious/spiritual identity. We found that while attendance, prayer/meditation, and religiosity had a statistical relationship with health outcomes, these relationships were frequently weak and often did not apply to people who were Nones, nonspiritual, or nonspiritual-Nones. Moreover, the results suggested that religious/spiritual identities moderated the relationship between religious/spiritual beliefs and behaviours, and health outcomes. Specifically, Nones, nonspiritual, and nonspiritual-Nones reported a nonpositive relationship between religion and health. Overall, the conclusion that "religion = better health" is an inadequate generalisation that fails to describe the nuance of the relationship.